Perancangan Buku Komik Kuliner Surabaya Sebagai Upaya Melestarikan Kuliner Tradisional - Shabrina, Mira; Karsam, Karsam; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
Surabaya, the capital of East Java province make Surabaya as center of business, education, industry, and trade. Many people from outside Surabaya like Madura, Madiun, Kertosono, Kediri, Gresik, Blitar, Ponorogo, and others who seek his fortune in the city of Surabaya, for example by selling food. So Surabaya has a diverse culinary variety. Unfortunately, the negative impact of globalization is such as the collapse of social institutions and the erosion of local culture. Traditions and local culture can become extinct slowly cause abandoned by their own people. This is certainly true for typical culinary Indonesia, which is part of the local culture. so  Therefore, this study aimed to create a culinary Surabaya comic book as an attempt to preserve traditional culinary. The design of this comic book using qualitative data collection methods, by interview, observation, documentation studies, literature, and existing studies are very important to define the concept design study. From the analysis of these data, the theme of the design concept obtained is Friendly. The concept was used for most of the design theme of the comic book, both of the characters, the plot, the color chosen, and so forth. Efforts to interest young people in reading this comic book one with a comic fullcolour more interesting than comic books culinary existing ones, using the drawing style of manga that is familiar among adolescents in the hope the comic book medium can be a medium that can preserve traditional cuisine and attract teenagers to the local culture.Kata Kunci: Buku, Komik, Kuliner, Surabaya, Kuliner Tradisional